Isolation and Optimization of Lipid Production from Drechslera Sp. and Feasibility of using Orange Peel as a Substrate for Growth - El-Shall, Hadeel Said (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2018)
This study deals with isolation and optimization of soil origin fungus Drechslera sp. with valued unsaturated fatty acids using orange peel as a substrate. Accordingly, to maximize oil production, various parameters were optimized using ’one variable at a time’ strategy followed by employing statistical designs (Plackett-Burman (PBD) & Response surface methodology (RSM)). The results showed that incubation time, FeSO4, pH and yeast extract were the most significant factors influencing lipid accumulation. Therefore, RSM employed to optimize their concentrations. The optimum parameter values were: incubation time 144 h, FeSO4 0.015 g/L, pH 8.5 and yeast extract 2 g/L. Under the optimized conditions, a total biomass of 12 g/L with a lipid content of 40.75 % (corresponding to a lipid yield of 4.89 g/L) was achieved. The fatty acid profile revealed production of 41.99 % of unsaturated fatty acids. The feasibility of utilizing orange peel as a sole carbon source proved that it represents a potentially valuable source of single cell oil (SCO) with oil yield of 3.65 g/L. Its FAME profile revealed an increment of unsaturated fatty acids up to 58.86% with desirable amounts of polyunsaturated fatty acids (PUFA) 33.31 %, this making it as ideal substrate for production of unsaturated fatty acids.